Nonmesonic weak decay of double- Λ hypernuclei: A microscopic approach - Bauer, Eduardo (2015)
The nonmesonic weak decay of double-Λ hypernuclei is studied within a microscopic diagrammatic approach. In addition to the nucleon-induced mechanism, ΛN→nN and ΛNN→nNN, widely studied in single-Λ hypernuclei, additional hyperon-induced mechanisms, ΛΛ→Λn, ΛΛ→Σ0n, and ΛΛ→Σ-p, are accessible in double-Λ hypernuclei and are investigated here. As in previous works on single-Λ hypernuclei, we adopt a nuclear matter formalism extended to finite nuclei via the local density approximation and a one-meson exchange weak transition potential (including the ground-state pseudoscalar and vector octets mesons) supplemented by correlated and uncorrelated two-pion-exchange contributions. The weak decay rates are evaluated for hypernuclei in the region of the experimentally accessible light hypernuclei ΛΛ10Be and ΛΛ13B. Our predictions are compared with a few previous evaluations. The rate for the ΛΛ→Λn decay is dominated by K-, K∗-, and η-exchange and turns out to be about 2.5% of the free Λ decay rate, ΓΛfree, while the total rate for the ΛΛ→Σ0n and ΛΛ→Σ-p decays, dominated by π-exchange, amounts to about 0.25% of ΓΛfree. The experimental measurement of these decays would be essential for the beginning of a systematic study of the nonmesonic decay of strangeness -2 hypernuclei. This field of research could also shed light on the possible existence and nature of the H dibaryon.